Federal Republic of Somalia Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2018)
To sustain its positive trajectory, Somalia needs to break out of its dual development trap, where inadequate resources and minimal trust in government are preventing the state from providing the public goods and services necessary to consolidate its legitimacy, while large periodic shocks (such as drought) reverse the gains made and endanger the welfare of the most vulnerable. To break out of this cycle and launch itself on a durable development trajectory, Somalia will need both improved institutions and predictable development financing. To take advantage of the opportunity provided by the current relative political stability, this systematic country diagnostic (SCD) applies a modified version of the changing wealth of nations framework. This framework is focused on building up sustainable national wealth rather than maximizing short-term consumption, and is based upon an assessment of the stocks of various forms of capital -natural assets like land, forests, fish, and minerals; productive assets like buildings, machinery, and infrastructure (such as highways, ports, and electricity generation); human assets (population, education, and health); as well as the intangibles (such as the quality of institutions, the vitality of the private sector, and the functioning of the society) that govern the functioning of the economy. In this framework, development is defined as the process of accumulating a diversified and growing portfolio of national wealth. Among other approaches, by differentiating intangible capital in terms of its social, institutional, and entrepreneurial aspects this SCD more explicitly captures the quality and capacity of public institutions and governance, the functioning of social safety nets, inclusion and the strength of dispute resolution systems, and entrepreneurship. It also makes it possible to identify such obstacles to development as constraints on the accumulation of capital or drivers of capital depletion.